TOK : a tangible interface for storytelling - Sylla, Cristina (2011)
We present the design of the first prototype of TOK - a tangible interface for children to create their own stories. Based on data collected with two groups of five years old preschoolers we present our findings regarding the interaction design of the system. The picture cards have shown to generate ideas, acting as input for the creation of stories, promoting creativity while proposing a framework that supports and guides the construction of logical structures. This is a first step in an effort to build a toolkit of tangible interfaces allowing children and teachers to build their own digital enhanced learning activities.